Performance study of millimetre‐wave MIMO channel in subway tunnel using directional antennas. Issue 5 (26th February 2018) - Jiang, Ye; Zheng, Guoxin; Yin, Xiaoyu; Saleem, Asad; Ai, Bo
Abstract : This study studies the multiple‐input–multiple‐output (MIMO) performance in a tunnel scenario for the millimetre‐wave (mm‐wave) band. We simulated and measured channel impulse response at 28 GHz for grids of transmitters and receivers to study the feasibility of mm‐wave MIMO system for metro communication in tunnel environment. The ray‐tracing method was utilised to obtain the MIMO channel matrices. The performance of the channel is studied in terms of 2 × 2 and 4 × 4 MIMO, and the influences of antenna spacing on the channel capacity are investigated. The results provide a reference for the fifth‐generation wireless network in the future communication‐based train control system applications.